1987
DOI: 10.1007/bf00393860
|View full text |Cite
|
Sign up to set email alerts
|

Stability and expression of transferred DNA in F1 tobacco transformants studied at various states of differentiation

Abstract: Grafts from the SR1 tobacco crown-gall lines NT1 (having a deletion eliminating part of the transferred (TL)-DNA auxin locus) and NT2 (having an IS60 insertion in gene 2 of this auxin locus) were cross-pollinated with pollen from nontransformed SR1 tobacco plants. One half of the resulting F1 progeny resembled the female parent ("transformed" NT1-like and NT2-like seedlings respectively) and one half resembled the male parent ("non-transformed" SR1-like seedlings). For three states of differentiation (callus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1987
1987
1994
1994

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…To investigate whether other TMV-inducible tobacco genes are also induced as a result of an elevated cytokinin concentration, the levels of mRNAs A -I in the shoot line SNT1005 were analysed. This line contains part of the octopine TL-DNA of Agrobacterium tumefaciens including an active cytokinin gene (T-cyt gene; [20]). Due to T-cyt-directed overproduction ofcytokinins SNT1005 shoots are unable to develop a root system and form numerous stunted side-sprouts.…”
Section: Induction Of Pr Genes As a Results Of Endogenous Overproductimentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate whether other TMV-inducible tobacco genes are also induced as a result of an elevated cytokinin concentration, the levels of mRNAs A -I in the shoot line SNT1005 were analysed. This line contains part of the octopine TL-DNA of Agrobacterium tumefaciens including an active cytokinin gene (T-cyt gene; [20]). Due to T-cyt-directed overproduction ofcytokinins SNT1005 shoots are unable to develop a root system and form numerous stunted side-sprouts.…”
Section: Induction Of Pr Genes As a Results Of Endogenous Overproductimentioning
confidence: 99%
“…Petit Havanna SR1 lines SNTI005 (T-DNA-transformed) and SNT1016 (untransformed) [20] were subcultured axenically at 26 °C and 2000 lux (12-h light cycle) on hormone-free LS medium at monthly intervals. Etiolated SNT1016 plants were obtained by growing subcultured plants for 3 weeks in the dark.…”
Section: P L a N T Tissuesmentioning
confidence: 99%
“…1D). Northern blots revealed that TL-DNA genes 5, 7 and 2 are not expressed in NT1 due to the deletion, whereas TL-DNA transcripts 1, 4, 6a/b and 3 were detected [14,20]. The absence of gene 2 implies that the TL-DNA auxin locus is not intact in NT1 (Aux-).…”
Section: Sr1-4013-3 + Is a Shooty Crown Gall Tumor Line Obtained Frommentioning
confidence: 99%
“…C: Extent of the T-region clone pOTY8 [6]. D: Extent of TL-DNA segment present in NT1 and NTl-like seedlings (including NT1.013) [14,20]. E: Open reading frames of genes on TL-DNA and TR-DNA according to Barker et al [2]; genes are numbered according to Willmitzer et al [26] (TL) and Salomon et al [23] (TR); genes which have a clear phenotypic effect, are hatched.…”
Section: Sr1-4013-3 + Is a Shooty Crown Gall Tumor Line Obtained Frommentioning
confidence: 99%
See 1 more Smart Citation